Photonic electric field sensor based on polymeric microspheres. Issue 3 (4th December 2013) - R. Ali, Amir; Ioppolo, Tindaro; Ötügen, Volkan; Christensen, Marc; MacFarlane, Duncan; Bunning, Timothy J.
ABSTRACT The detection of electric field by monitoring the optical whispering gallery mode shifts of polymeric microspheres is demonstrated. Two types of spheres are considered; (i) a polydimethylsiloxane (PDMS) sphere with 60 parts base silicon elastomer‐to‐1 part polymer curing agent by volume and; (ii) a silica sphere coated with a PDMS (uncured) base. The optical mode shifts are caused by perturbations to the resonator morphology induced by electrostriction effect in the presence of an external electric field. Preliminary experiments show that the latter microsphere yields higher sensitivity (0.027 pm/V m−1) with a measurement precision of ∼1.8 V/m. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 276–279